The Ability of Students to Explain Science Concepts in Two Languages - Airey, John (HERMES - Journal of Language and Communication in Business, 2010)
This paper analyses the ability of twenty-one physics undergraduates at two Swedish universities to orally describe and explain in both Swedish and English the science concepts met in their lectures. This ability is related back to the language used to teach the concepts (English, Swedish or both languages). Transcripts of student descriptions in both languages are rated using three measures: 1. Fluency (in terms of syllables per second and mean length of runs) 2. Code-switching 3. A judgment about the ‘disciplinarity’ of what is said. Comparison between languages ﬁnds that students speak on average 45% slower and have 33% shorter runs in their English descriptions. However, these differences in speaking rate and run length become much lower (28% and 26% respectively) in those transcripts where students appear to have adequately understood the concepts that were presented in the lectures. These latter values are in line with ﬁndings in comparative studies of other types of speech event (See Hincks 2010). Analysis of code-switching identiﬁes some students (n=3) who have great difﬁculty describing disciplinary concepts in English. These were ﬁrst year students and were being taught in English for the ﬁrst time. It is thus concluded that for some students disciplinary English is indeed a problem. However, from a disciplinary point of view, all other students give similarly good (or bad) descriptions of physics concepts in both Swedish and English, regardless of the language used in the lectures.